CEDAR-GPP: spatiotemporally upscaled estimates of gross primary productivity incorporating CO2 fertilization - Y. Kang; Y. Kang; Y. Kang; M. Bassiouni; M. Bassiouni; M. Gaber; M. Gaber; X. Lu; X. Lu; T. F. Keenan; T. F. Keenan (Earth System Science Data)
Gross primary productivity (GPP) is the largest carbon flux in the Earth system, playing a crucial role in removing atmospheric carbon dioxide and providing carbohydrates needed for ecosystem metabolism. Despite the importance of GPP, however, existing estimates present significant uncertainties and discrepancies. A key issue is the underrepresentation of the CO2 fertilization effect, a major factor contributing to the increased terrestrial carbon sink over recent decades. This omission could potentially bias our understanding of ecosystem responses to climate change.